Tenderness and intramuscular lipid of most major muscles from Bos indicus cattle are less than Bos taurus cattle - C.M. Highfill; O.E. Font; Donald H. Kropf; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 2011)
In semitropical climates in the United States, Bos indicus breeds of cattle, primarily the Brahman breed, are utilized in crossbreeding programs with Bos taurus cattle to improve productivity by increasing disease and insect resistance, heat tolerance, heterosis, and additive genetic variation. About 25% of the U.S. beef population contains some Bos indicus breeding. Numerous published reports show that tenderness of ribeye and strip loin steaks and marbling are significantly reduced in Bos indicus straightbred or crossbred cattle compared to most Bos taurus breeds. One very large study reported that heritability of tenderness and marbling is around 0.4, making it a positive trait to try to improve through selection. Only one published report has compared tenderness differences between Bos indicus and Bos taurus cattle for more than the ribeye and strip loin (longissimus muscle) and that study showed that other muscles were less tender for Bos indicus cattle. The objectives of our study were: (1) to compare carcass traits between Hereford x Angus crossbred cattle with those containing at least 50% Brahman and Sahiwal inheritance, and (2) to validate Warner-Bratzler shear force of steaks and roasts and proximate composition of 10 different muscles from these cattle.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen& #x27; s Day; 2011; Beef; Tenderness; Bos indicus; Bos taurus; Warner-Bratzler shear machine; Marbling